Meningkatkan Hasil Belajar Penjumlahan Bilangan Asli melalui Pendekatan Matematika Realistik pada Siswa SD - Ngadilah Ngadilah; Ana Fitrotun Nisa; Banun Hanifah Cahyo Khosiyono; Berliana Henu Cahyani (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
This study was motivated by the problem of the lack of students' ability in mathematics subjects, especially in the addition of natural numbers, which also affects the learning outcomes. This research was conducted to determine how the implementation of Realistic Mathematics Approach method can optimise students' learning outcomes in the addition of natural numbers. The participants in this study were students of class 1A Timuran Elementary school, Kemantren Mergangsan, Yogyakarta City. This study used the Classroom Action Research (CAR) method with the Kemmis and McTaggart model consisting of two cycles, where each cycle included two meetings. The instruments used includes test sheets and observation sheets. Data were analysed using qualitative and quantitative methods, where qualitative analysis was carried out descriptively, while quantitative analysis was carried out by calculating the average value. The research findings indicated an improvement in students' learning outcomes, which was seen in the cognitive results of students when taking the test. In cycle 1 meeting 1, the percentage of classical completeness reached 60% with an average of 67.86. In cycle 1 meeting 2, the percentage of completeness increased to 70% with an average of 76.79. Cycle 2 meeting 1 showed further improvement with 82% completeness and an average of 83.93, while in cycle 2 meeting 2, classical completeness reached 100% with an average of 88.57. This study concluded that the application of Realistic Mathematics Approach was effective in improving students' learning outcomes in mathematics subjects, especially the addition of natural numbers.